In and out: Leishmania metastasis by hijacking lymphatic system and migrating immune cells - Jha, Baijayanti; Reverte, Marta; Ronet, Catherine; Prevel, Florence; Morgenthaler, Florence D.; Desponds, Chantal; Lye, Lon-Fye; Owens, Katherine L.; Scarpellino, Leonardo; Dubey, Lalit Kumar; Sabine, Amélie; Petrova, Tatiana V.; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
The lymphatic system plays a crucial role in mounting immune response against intracellular pathogens and recent studies have documented its role in facilitating tumor dissemination linked largely with cancer cells. However, in Mucocutaneous leishmaniasis (MCL) caused by Leishmania Viannia subgenus showing infectious metastasis and resulting in severe distant secondary lesions, the route of escape of these parasites to secondary sites has not yet been investigated in details. Our results demonstrated that when infection was associated with inflammation and additionally exacerbated by the presence of dsRNA viral endosymbiont (LRV1), lymphatic vessels could serve as efficient routes for infected cells to egress from the primary site and colonize distant organs. We challenged this hypothesis by using an intracellular Leishmania protozoan parasites Leishmania guyanensis (Lgy) associated with or without a double –stranded RNA (dsRNA) viral endosymbiont, exacerbating the infection and responsible for a strong inflammatory response and favoring metastasis of the infection. We analyzed possible cargo cells and the routes of dissemination though flow cytometry, histological analysis and in vivo imaging in our metastatic model to show that parasites disseminated not only intracellularly but also as free extracellular parasites using migrating immune cells, lymph nodes (LNs) and lymph vessels, and followed intricate connections of draining and non-draining lymph node to finally end up in the blood and in distant skin to cause new lesions.